2023
DOI: 10.2147/nss.s386021
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Severity and Treatment Satisfaction in Patients with Idiopathic Hypersomnia: The Real World Idiopathic Hypersomnia Outcomes Study (ARISE)

Abstract: Idiopathic hypersomnia is a debilitating sleep disorder characterized by excessive daytime sleepiness, sleep inertia, and prolonged sleep duration. The patient burden of idiopathic hypersomnia is poorly understood. The Real World Idiopathic Hypersomnia Outcomes Study (ARISE) evaluated symptoms and treatment effectiveness/satisfaction in participants with idiopathic hypersomnia. Methods: ARISE was a United States-based virtual cross-sectional survey. Participants were adults 21-65 years of age with idiopathic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…An important point is that these impairments were observed despite most participants (89.3%) taking off-label medications to treat idiopathic hypersomnia, primarily stimulants, wake-promoting agents, and antidepressants. 15 This suggests that off-label treatment options are not sufficient to manage symptoms in most people with idiopathic hypersomnia. Baseline scores for daily functioning and work productivity were similarly low in participants of a Phase 3 trial (of whom 55.8% were taking off-label alerting agents), which further supports the inadequacy of off-label treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important point is that these impairments were observed despite most participants (89.3%) taking off-label medications to treat idiopathic hypersomnia, primarily stimulants, wake-promoting agents, and antidepressants. 15 This suggests that off-label treatment options are not sufficient to manage symptoms in most people with idiopathic hypersomnia. Baseline scores for daily functioning and work productivity were similarly low in participants of a Phase 3 trial (of whom 55.8% were taking off-label alerting agents), which further supports the inadequacy of off-label treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…The ARISE study also assessed symptom severity and treatment effectiveness/satisfaction, which are reported in a separate publication. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic interventions include lifestyle modifications and preventive therapy focusing on factors such as sleep hygiene (eg, discontinuation of electronics use well before bedtime), adjustment of work hours (eg, beginning work later in the day rather than early morning), regular exercise, and a healthy diet. [42][43][44] In addition, cognitive behavioral therapy for hypersomnia emphasizes education about the disease state, self-identity and self-image (including strategies for self-acceptance), structured daytime and nighttime activities, coping skills and emotional regulation, social support, and medical/legal/occupational issues (eg, potential accommodations). 45 As far as pharmacologic approaches, narcolepsy and idiopathic hypersomnia are often treated offlabel, and treatment is generally symptomatic (eg, EDS and cataplexy) due to poor understanding of the pathophysiology of NT2 and idiopathic hypersomnia.…”
Section: Treatment Of Narcolepsy and Idiopathic Hypersomniamentioning
confidence: 99%
“…It has been reported that individuals with IH experience more anxiety and depression compared to those without IH [ 3 ]. Patients with IH often describe experiencing autonomic symptoms such as headaches, temperature dysregulation, and fainting more frequently as compared to healthy individuals [ 4 ]. Idiopathic hypersomnia can thus negatively affect many aspects of daily life.…”
Section: Introductionmentioning
confidence: 99%
“…However, the approval of modafinil for IH in Europe was rescinded in 2011 after a re-evaluation found insufficient evidence to support the indication for its use and after reports of rare severe skin reactions [ 7 ]. Unfortunately, most individuals with IH still cannot function well in many areas of their lives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%